THE RELATIONSHIP BETWEEN INTERNET ADDICTION AND LEARNING ACHIEVEMENT - Maryuti, Ira Ayu; Astarini, Made Indra Ayu; Pae, Kristina; Bura Mare, Agustina Chriswinda (Jambura Nursing Journal, 2025)
Internet usage has increased sharply due to technological developments, especially since the pandemic that occurred some time ago. Limitations in meeting face to face, finally gave rise to ideas for using internet media to complete tasks or achieve certain goals both in education and work. People who are addicted to the internet show an uncontrolled life so that sufferers cannot leave the internet. Internet addiction is the inability of an individual to control their internet usage, which can cause psychological, social and work (educational) problems in the individual's life. This study aims to analyze the effect of internet addiction on learning achievement.This study is a Spearman Rank correlation study. The respondents were 100 students of Nurul Huda Kapongan Middle School. The sampling technique was purposive sampling. Data collection using an internet addiction test questionnaire with 20 question items, while for learning achievement using report card scores. The results of the study based on the hypothesis test carried out obtained p = 0.809 (> 0.05). Where these results indicate that there is no relationship between internet addiction and learning achievement